Direct payment of Housing Benefit: responsibilisation at what cost to landlords?. Issue 4 (2nd October 2019) - Wilson, Ian
Abstract: Income-related housing allowances are used by most advanced welfare states to ensure that their citizens have access to decent accommodation at a price within their means. Surprisingly, comparing outcomes when the subsidy is paid to the claimant or direct to the landlord has attracted little attention, despite differences existing between countries. This paper uses data collected as part of the evaluation of the Direct Payment Demonstration Projects (DPDPs) in Great Britain to test the impact on rent collection and arrears of paying Housing Benefit to tenants, as oppose to the landlord direct. The DPDPs aimed to provide learning in readiness for the introduction of Universal Credit, which sees six separate benefits consolidated into one monthly payment made to the claimant. Using quasi-experimental rental account analysis techniques, the direct payment was found to have a significant negative effect on both rent collection and arrears. However, evidence suggested that the longer term impact may be smaller as tenants become more 'normalised' to having responsibility for paying their rent. These findings make an important contribution to the major theoretical debate on the effectiveness of using welfare policy to promote 'responsibilisation', which has become the dominant discourse since the mid-late 1990's.